The Process Of An Extradition Request To Ecuador United States Embassy In England (Analysis Of Juridical Cases Wikileaks Founder Julian Assange Of Crime Espionage) - Hermaya Anita, Dadang Siswanto *), Peni Susetyorini (Diponegoro Law Journal, 2013)
Extradition is a formal handover which done either by the extradition treaty which was held earlier or on the basis of reciprocity, the person accused of a criminal act (the suspect, accused, defendant) or the person who has been sentenced for his crime (convicted, sentenced), the countries in which it escaped or was or hiding, the country that has the jurisdiction to prosecute or punish, as by the request of the country. From the definition can be discovered extradition contains various elements, these elements can be done from the U.S. extradition request to the Embassy of Ecuador in the UK and espionage related to the crimes committed by Julian Assange. The process of extradition requests can only be made by the country to the country, not the country with the embassy, and requests can be submitted in a formal extradition through diplomatic channels of each country. Extradition is a process based on a principle of reciprocity or by an agreements between countries. The U.S. extradition request procedure to the Ecuadorian Embassy in the UK is not in accordance with the provisions of the extradition procedure in general, due to the procedure for submission of requests and procedures to deliver or reject the submission itself with all it has to do through diplomatic channels. Espionage crime is a spy activities (intelligence / espionage) in order to gather information without the knowledge and consent of the person or institution concerned. And there is a principle of extradition which does not deliver a political crime as it relates to the universally recognized human rights which has been set out in the 1948 UDHR and 1966 ICCPR. So it can be seen that the crime of espionage is part of a political crime that can not be extradited